Six Motivations of Housewives Following the Tahsin Alquran - Oktavia, Gifa; Ramadhany, Nur Fadilah; Sabrina, Vinni; Sameto, Mayang Belia (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2020)
This research aims to determine the motivation of housewives in participating in the Alquran tahsin program in West Sumatra. This research uses a qualitative research method with a phenomenological approach. In this study, researchers focused on discussing the motivation of housewives in participating in the tahsin program. Data sources were taken from twenty-five informants through in-depth interviews accompanied by documentation of activities. The informants were housewives who took part in the Quran tahsin program and two tahsin teachers. All interview results were then analyzed theoretically using software NVivo 12 qualitative analysis. The results of the analysis show that there are six motivations that come from within and outside the participants of the Alquran tahsin program. Housewives' intrinsic motivation can be seen from i) their own desire to be able to read the Alquran, ii) they feel they lack knowledge of the Quran, iii) they have never studied the Quran since childhood. Furthermore, the extrinsic motivation for housewives in participating in the Alquran tahsin program is: iv) the priority of people who are proficient in reading the Quran being gathered together with noble angels, v) being invited by friends, vi) learning methods that are easy for teachers to understand. This research has succeeded in revealing the intrinsic and extrinsic motivation of housewives in participating in the Tahsin Alquran program. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.